SWOT Analysis of the Benefits of Hydropower Energy in Four Archipelagos - Cruz-Pérez, Noelia; Rodríguez-Alcántara, Joselin S.; Koronaiou, Vasiliki L. P.; Jančula, Anja; Rodríguez-Martín, Jesica; García-Gil, Alejandro; Fontes, José C.; Santamarta, Juan C. (Civil Engineering Journal, 2024)
Increasing energy production through renewable sources is a challenge for islands. This paper investigates the potential of hydropower as a renewable energy source for islands in the Macaronesia region, which includes the Azores, Madeira, Canary Islands, and Cape Verde. Ecological transition towards renewable energy sources is crucial for these islands due to their current dependence on imported fossil fuels and their remoteness. The methodology used in this paper combines a SWOT analysis with a review of relevant literature. The SWOT analysis evaluates the Strengths, Weaknesses, Opportunities, and Threats associated with hydropower development on each island. The results show that each island has unique characteristics that influence its hydropower potential. The Azores has existing mini-hydropower plants and opportunities for pumped storage systems due to its rainfall and volcanic features. Madeira also utilizes hydropower, including the world's first underground pumped storage plant (UPHS) in Socorridos. However, limitations exist due to the mountainous terrain and competition for water resources. The Canary Islands showcase the success story of El Hierro Island, which significantly increased renewable energy penetration through a wind farm and pumped storage hydropower system. The topography and lack of rainfall on Cape Verde make the development of hydropower a significant challenge and, as a result, the focus has shifted to wind power. The study concludes that hydropower can play a significant role in the ecological transition of these islands. However, careful planning and consideration of environmental factors are necessary to maximize the benefits and minimize the potential drawbacks. The paper emphasizes the importance of island-specific assessments and exploring opportunities for pumped storage systems. Doi: 10.28991/CEJ-2024-010-07-019 Full Text: PDF